An African American Student Networking Group in an Urban High School: Experiences and Outcomes. (November 2019) - Gbolo, Simone; Grier-Reed, Tabitha LaShaun
Educational disparities are deeply entrenched in U.S. society. Our research focused on a move toward equity and investment in one Midwestern charter school via the implementation of the African American Student Network. Participants were 15 male and 15 female students in Grades 9 to 12 who participated in the network for one semester. Qualitative analysis of focus group interviews revealed that students in the network experienced safety, support, empowerment, affirmation, and connectedness. Quantitative analysis revealed that pre- and post-test grade point averages (GPAs), disciplinary referrals, and attendance trended in promising directions although there were no statistically significant differences.